Statistical analysis on mechanical properties of friction-stir-welded AA 1050/AA 5083 couples - Sarsilmaz, Furkan; Caydas, Ulas (Springer London Ltd, 2009)
In this study, the effect of friction-stir welding (FSW) parameters such as spindle rotational speed, traverse speed, and stirrer geometry on mechanical properties of AA 1050/AA 5083 alloy couples were experimentally investigated. Ultimate tensile strength (UTS) and hardness of welded joints were determined for this purpose. The full-factorial experimental design was conducted to obtain the response measurements. Analysis of variance (ANOVA) and main effect plot were used to determine the significant parameters and set the optimal level for each parameter. A linear regression equation was derived to predict each output characteristic. The experimental and predicted values were in a good agreement with a R (2) of 0.82 and 0.93 for UTS and hardness, respectively.
Keywords: Friction-stir welding; ANOVA; DOE; Aluminum alloys